1988
DOI: 10.1093/bja/61.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Kinetics of Fentanyl and Alfentanil in Surgical Patients

Abstract: Lipid-soluble basic drugs may be sequestered as the drug-loaded blood passes through the pulmonary capillaries [1], and the amount of drug remaining in the blood for distribution to the organism may be substantially reduced by this mechanism. The temporary sequestration of a significant proportion of an i.v. dose of a drug by the lung may influence the intensity and duration of its pharmacological effect [2]. Hess, Herz and Friedel [3] reported that rabbit lung had a high affinity for fentanyl: approximately 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 24 publications
0
13
1
1
Order By: Relevance
“…Entretanto, estes benefícios podem ser superados por algumas propriedades adversas destes agentes, dentre elas a supressão da vasoconstrição pulmonar hipóxica e da broncoconstrição hipocápnica 50 , além da depressão da resposta imunológica pulmonar, função já comprometida em idosos 51 . Taeger e col. relataram que uma alta percentagem de fentanil e alfentanil é seqües-trada no pulmão após administração venosa, sugerindo que o sítio de ligação pode estar localizado no surfactante alveolar 52 . Por outro lado, a ação dos opióides na musculatura lisa causa broncoconstrição 53 .…”
Section: Mortalidade E Morbidade Pulmonar Pós-operatóriaunclassified
See 1 more Smart Citation
“…Entretanto, estes benefícios podem ser superados por algumas propriedades adversas destes agentes, dentre elas a supressão da vasoconstrição pulmonar hipóxica e da broncoconstrição hipocápnica 50 , além da depressão da resposta imunológica pulmonar, função já comprometida em idosos 51 . Taeger e col. relataram que uma alta percentagem de fentanil e alfentanil é seqües-trada no pulmão após administração venosa, sugerindo que o sítio de ligação pode estar localizado no surfactante alveolar 52 . Por outro lado, a ação dos opióides na musculatura lisa causa broncoconstrição 53 .…”
Section: Mortalidade E Morbidade Pulmonar Pós-operatóriaunclassified
“…These benefits, however, may be overridden by some adverse properties of such agents, among them hypoxic pulmonary vasoconstriction and hypocapnic bronchoconstriction suppression 50 , in addition to pulmonary immune response depression, which is already affected in the elderly 51 . Taeger et al have reported that a high percentage of fentanyl is scavenged in the lungs after intravenous administration, suggesting that the binding site may be located on the alveolar surfactant 52 . On the other hand, the action of opioids on smooth muscles causes bronchoconstriction 53 .…”
Section: Anesthetic Managementmentioning
confidence: 99%
“…6 In spite of the great number of studies dedicated to the use of opioids during anesthesia, few data are available regarding the effects of last generation opioids on respiratory mechanics under general anesthesia. [7][8][9] A previous study has evaluated the effects on respiratory mechanics of high-dose alfentanil administration in patients undergoing cardiac surgery. 10 The aim of this study was to evaluate the effects of alfentanil administration on respiratory system mechanics in a group of ASA I patients mechanically ventilated during general anesthesia for general surgery.…”
Section: éLéments Cliniques : Vingt Patients Consécutifs Asa I Ont éTmentioning
confidence: 99%
“…Means i s.d. Lung uptake of many basic drugs has recently been demonstrated (22)(23)(24). Thiopentone is eliminated mainly by metabolism in the liver (21), but it has a low hepatic extraction ratio ( 13).…”
Section: Discussionmentioning
confidence: 99%